Police vs. protests of Women’s Movement in Poland – criminological and sociological perspective: Police vs. the Women’s Movement protests in Poland – a criminological and sociological perspective (Archives of Criminology, 2022)
This article deals with one of the most discussed issues in Poland in 2020 (alongside the COVID-19 pandemic and the presidential election) – abortion, and the women’s protests that sprang up during a critical situation for society – the COVID-19 pandemic. The unexpected publication of the Constitutional Court’s judgment split Poland into several camps. Numerous intense debates were also caused by the actions of the police officers securing the gathering. Although there are many sources examining the women’s protests, they have usually focused on either statements from participants or police spokespersons. The author decided to look at these issues from a different research perspective – from the perspective of police officers, with whom she conducted anonymous in-depth interviews.